Policies for healthy ageing in response to climate change: Protocol of a systematic review - Nestor Asiamah; Bernard Opoku Ofosu; Yaw Jnr Effah-Baafi; Kofi Awuviry-Newton; Jacob Nkansah; Bernadette Saunders (PLoS ONE, 2025)
Climate change is a global phenomenon affecting every segment of the population. Yet, older adults are more vulnerable to climate change events (e.g., floods, heatwaves, landslides) owing to their functional limitations. Understandably, stakeholders have called for healthy ageing policies that enable older adults and individuals in the general population to maintain wellbeing despite climate change. This review aims to describe healthy ageing policies adopted or recommended in response to climate change. Eight databases (i.e., CINAHL, Cochrane library, ProQuest, PsycINFO, Google Scholar, Web of Science, Scopus, and MEDLINE) will be searched to identify relevant studies. Materials published anywhere in English to date will be included in the review. The Critical Appraisal Skills Programme (CASP) or Joanna Briggs Institute (JBI) checklist will be employed to assess the quality of studies. A narrative synthesis will be adopted to present the results. This review will highlight groups targeted with healthy ageing policies and describe policies in use or recommended. It will proffer implications for practice, research, and sustainability.